О престолонаследии в древнехеттском царстве (К интерпретации § 28 « Указа Телипину ») - Гиоргадзе, Г. Г.
Giorgadze, G. G.; The Order of Succession to the throne in the Old Hittite Kingdom (On the Interpretation of § 28 in the “Decree of Telipinu”); engl. Résumé.